Antibacterial, antibiofilm and anti-quorum sensing activities of 1,2,3,5-tetrazine derivatives linked to a benzothiazole moiety - Jean Paul Dzoyem; Joseph Tsemeugne; Boniface Pone Kamdem; Rostand Foyou Meupiap; Boris Arnaud Kuate; Pierre Mkounga; Fabrice Fekam Boyom; Lyndy Joy McGaw (PLoS ONE, 2025)
A series of known tetrazine derivatives, containing benzothiazole scaffold, were prepared during the coupling reactions of selected diazotized 2-aminobenzo[d]thiazole derivatives with p-acetaminophen. The as-prepared compounds were characterized based on NMR and MS spectrometry. The antibacterial and anti-biofilm activities of the synthesized compounds were evaluated by microdilution method, whereas the anti-quorum sensing effect was carried out using assay for the inhibition of violacein formation. As a result, compounds 4a , 4b and 4c revealed minimum inhibitory concentrations and minimum bactericidal concentrations ranging from 8 to 128 µg/mL and from 32 to 256 µg/mL, respectively. Compounds 4a (52–86.5%), 4b (57.7–79.4%) and 4c (59.9–80.3%) prevented biofilm formation in all the four bacteria tested with percentages of inhibition more than 50%. The concentrations of 4a , 4b and 4c that inhibited 50% of violacein production were found to be 62.71, 28.56 and 107.45 µg/mL, respectively, thus attesting that these compounds possess anti-quorum sensing activity. Noteworthy, our previous investigation attested that these compounds are non-cytotoxic on the human mammalian cells Vero. This novel contribution demonstrates the antibacterial, antibiofilm and anti-quorum sensing activities of tetrazine-based benzothiazoles, which might be prospected as scaffolds for the discovery of efficient antibiotics with decreased risk of microbial drug resistance.